2011
DOI: 10.2308/bria-10063
|View full text |Cite
|
Sign up to set email alerts
|

Does the Arrangement of Audit Evidence According to Causal Connections Make Auditors More Susceptible to Memory Conjunction Errors?

Abstract: Although prior research has shown that arranging working paper evidence according to causality can improve auditor judgment, the present study proposes that causal arrangements may elicit certain ill-effects on auditor memory and thus undermine auditor judgment. Specifically, causal arrangements of evidence may heighten auditors' vulnerability to memory conjunction errors (MCEs), wherein auditors misattribute one client's evidence to another client. In an experiment, auditors provided going concern judgments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Grossman and Welker (2011) extend this research by showing that auditors’ propensity to commit memory conjunction errors is higher when audit evidence is arranged in a causal sequence rather than in a traditional working paper order or random order. However, Bhattacharjee et al (2007, 2017) find that even when memory bits are attributed to the proper client, judgment errors may occur as a result of contrast effects.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 81%
See 1 more Smart Citation
“…Grossman and Welker (2011) extend this research by showing that auditors’ propensity to commit memory conjunction errors is higher when audit evidence is arranged in a causal sequence rather than in a traditional working paper order or random order. However, Bhattacharjee et al (2007, 2017) find that even when memory bits are attributed to the proper client, judgment errors may occur as a result of contrast effects.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 81%
“…Complementing O’Donnell and Schultz’s (2005) investigation of judgment effects resulting from the performance of multiple tasks for a single client is research on judgment effects stemming from the performance of similar tasks for multiple clients. For example, Lindberg and Maletta (2003) and Grossman and Welker (2011) document how auditors commit memory conjunction errors when their multitasking involves more than one audit client. According to Lindberg and Maletta (2003), memory conjunction errors transpire when memory bits related to one situation are improperly associated with another situation during the memory reconstruction process.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Table (4) evaluates how the topics are evaluated based on a 50-point index in the form of scores from 1 to 5 based on the 10 criteria described. The scores presented based on the fashion index showed that out of a total of 12 initial pieces of research, three kinds of research by Mubako and Donnell (2018); Grossman andWelker (2011), andAbednazari et al (2018) considering that out of 50 points, they received less than 30, and in accordance with the guidelines for the adequacy of the score of this analysis, studies that have a score of 30 or higher are approved, were eliminated, and for this reason, they were removed from the investigation. Then, using the Trade-Sterling method ( 2001), research propositions are extracted.…”
Section: B) Identify the Themes Of The Auditors' Mindset (L)mentioning
confidence: 99%